MELD-GRAIL and MELD-GRAIL-Na Are Not Superior to MELD or MELD-Na in Predicting Liver Transplant Waiting List Mortality at a Single-center Level. Issue 7 (10th June 2022) - Chetwood, John D.; Wells, Mark G.; Tsoutsman, Tatiana; Pulitano, Carlo; Crawford, Michael D.; Liu, Ken; Strasser, Simone I.; McCaughan, Geoffrey W.; Majumdar, Avik
Abstract : Background: Controversy exists regarding the best predictive model of liver transplant waiting list (WL) mortality. Models for end-stage liver disease–glomerular filtration rate assessment in liver disease (MELD-GRAIL) and MELD-GRAIL-Na were recently described to provide better prognostication, particularly in females. We evaluated the performance of these scores compared to MELD and MELD-Na. Methods: Consecutive patients with cirrhosis waitlisted for liver transplant from 1998 to 2017 were examined in this single-center study. The primary outcome was 90-d WL mortality. MELD, MELD-Na, MELD-GRAIL, and MELD-GRAIL-Na at the time of WL registration were compared. Model discrimination was assessed with area under the receiver operating characteristic curves and Harrell's C-index after fitting Cox models. Model calibration was examined with Grønnesby and Borgan's modification of the Hosmer-Lemeshow formula and by comparing predicted/observed outcomes across model strata. Results: The study population comprised 1108 patients with a median age of 53.5 (interquartile range 48–59) y and male predominance (74.9%). All models had excellent areas under the receiver operating characteristic curves for the primary outcome (MELD 0.89, MELD-Na 0.91, MELD-GRAIL 0.89, MELD-GRAIL-Na 0.89; all comparisons P > 0.05). Youden index cutoffs for 90-d mortality were as follows: MELD, 19; MELD-Na, 22; MELD-GRAIL, 18; and MELD-GRAIL-Na, 17. Variables associated with 90-d mortality on multivariable Cox regression were sodium, bilirubin, creatinine, and international normalized ratio. There were no differences in model discrimination using Harrell's C-index. All models were well calibrated; however, divergence between observed and predicted mortality was noted with scores ≥25. Conclusion: There were no demonstrable differences in discrimination or calibration of GRAIL-based models compared with MELD or MELD-Na in our cohort. This suggests that GRAIL-based models may not have meaningful improvements in discriminatory ability when applied to other settings.